2011
DOI: 10.5505/agri.2011.82788
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the analgesic effects of intravenous paracetamol and lornoxicam in postoperative pain following thyroidectomies

Abstract: Administration of iv lornoxicam and iv paracetamol following thyroid surgery decreased the postoperative pain scores and opioid requirement, as well as the incidence of nausea and vomiting, while also prolonging the time to the first analgesic supplement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
(25 reference statements)
0
7
0
2
Order By: Relevance
“…In previous our study we reported also preventive epidural analgesia with bupivacaine and fentanyl associated with the lower pain scores and opioid requirements postoperatively in patients undergoing major gynecologic surgery (15). A dose of 1gr paracetamol given before the end of surgery, the same dose of paracetamol given in other studies (16,17). Although Juhl GIet al (18).…”
Section: Discussionmentioning
confidence: 96%
“…In previous our study we reported also preventive epidural analgesia with bupivacaine and fentanyl associated with the lower pain scores and opioid requirements postoperatively in patients undergoing major gynecologic surgery (15). A dose of 1gr paracetamol given before the end of surgery, the same dose of paracetamol given in other studies (16,17). Although Juhl GIet al (18).…”
Section: Discussionmentioning
confidence: 96%
“…There was a significant reduction in the incidence of nausea and vomiting and also significantly prolonged the time for the first rescue analgesic requirement. 31 All the mentioned studies in the article demonstrate the efficacy of lornoxicam as a pre emptive analgesic agent in a variety of surgical procedures. In our study we tried to analyze the efficacy of lornoxicam in the abdominal surgery patients when used as a preemptive analgesic agent for the reduction of post-operative pain and for subsequent reduction in the requirement of Opioid analgesics.…”
Section: Discussionmentioning
confidence: 95%
“…The reduction in total opioid consumption may also be due to the opioid sparing effect of pre-emptive Paracetamol which has been seen in other studies as well. 20,11 The reduction of this dose during the first days of treatment is an important factor in improving tolerability. The most common adverse effects of opioid are nausea, vomiting, respiratory depression, dizziness, fatigue, sweating, dry mouth, drowsiness and orthostatic hypotension.…”
Section: Discussionmentioning
confidence: 99%
“…Opioid commonly used in post operative period has considerable side effect like nausea and vomiting. 4,5 Pre-emptive analgesia with I.V Paracetamol reduces the opioid requirement, thus reducing the nausea and vomiting. Paracetamol inhibits the release of prostaglandin in the spinal cord, also has effect on serotonin mechanism for spinal pain inhibation.…”
Section: Introductionmentioning
confidence: 99%